Relationship Between Recurrence of Chronic Subdural Hematoma with its Preoperative Volume (Bangladesh Journal of Neurosurgery, 2022)
Background: Chronic subdural hematoma (CSDH) is commonly encountered in neurosurgical practice. However, surgical evacuation remains complicated by a high rate of recurrence.Objective: To assess the relationship between preoperative volume of chronic subdural hematoma and its post-operative recurrence.Methods: This hospital based prospective observational study was carried out in the Department of Neurosurgery, Chittagong Medical College Hospital (CMCH), Chattogram during April 2017 to October 2018. A total of 130 patients clinically and radiologically diagnosed with CSDH and underwent surgery were enrolled in the study. Patients were followed up for 6 months postoperatively to observe the recurrence rate by symptom evaluation and radiological investigation.Results: Mean age of the study population was 65.77 (±14.83) years with a range of 18-95 years where 81.5% were male. Among the patients, 51.5% (n=67) had history of trauma and 16.2% (n=21) used anti-coagulant. CT scan finding showed that 20.8% (n=27) had bilateral hematoma, 73.8% (n=96) had e”2 cm thickness of hematoma whereas 70.8% (n=92) had e”1 cm midline shifting. The mean pre-operative volume was 133.36 (±60.26) ml where 40.0% (n=52) had